Construction of double reaction zones for long-life quasi-solid aluminum-ion batteries by realizing maximum electron transfer - Yu, Zhijing; Wang, Wei; Zhu, Yong; Song, Wei-Li; Huang, Zheng; Wang, Zhe; Jiao, Shuqiang (Nature communications, 2023)
Achieving high energy density and long cycling life simultaneously remains the most critical challenge for aluminum-ion batteries (AIBs), especially for high-capacity conversion-type positive electrodes suffering from shuttle effect in strongly acidic electrolytes. Herein, we develop a layered quasi-solid AIBs system with double reaction zones (DRZs, Zone 1 and Zone 2) to address such issues. Zone 1 is designed to accelerate reaction kinetics by improving wetting ability of quasi-solid electrolyte to active materials. A composite three-dimensional conductive framework (Zone 2) interwoven by gel network for ion conduction and carbon nanotube network as electronic conductor, can fix the active materials dissolved from Zone 1 to allow for continuing electrochemical reactions. Therefore, a maximum electron transfer is realized for the conversion-type mateials in DRZs, and an ultrahigh capacity (400 mAh g −1 ) and an ultralong cycling life (4000 cycles) are achieved. Such strategy provides a new perspective for constructing high-energy-density and long-life AIBs. Achieving high energy density and long cycling life simultaneously remains a critical challenge for aluminum-ion batteries. Here, the authors develop a layered quasi-solid battery with double reaction zones to suppress shuttle effect of conversion-type materials and improve both energy density and cycling life.